2013
DOI: 10.1016/j.cmet.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Subtype-Selective Recruitment of TLE3 or Prdm16 by PPARγ Specifies Lipid Storage versus Thermogenic Gene Programs

Abstract: Transcriptional effectors of white adipocyte-selective gene expression have not been described. Here we show that TLE3 is a white-selective cofactor that acts reciprocally with the brown-selective cofactor Prdm16 to specify lipid storage and thermogenic gene programs. Occupancy of TLE3 and Prdm16 on certain promoters is mutually exclusive, due to the ability of TLE3 to disrupt the physical interaction between Prdm16 and PPARγ. When expressed at elevated levels in brown fat, TLE3 counters Prdm16, suppressing br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(148 citation statements)
references
References 46 publications
(72 reference statements)
10
136
0
Order By: Relevance
“…Interestingly, we examined the expression of the two very recently described genes Ehmt1 and Tle3 {transducin-like enhancer of split 3 [E(sp1) homolog, Drosophila]}, which stabilize and counter Prdm16 activity, respectively. Rodents lacking Ehmt1 and Tle3 displayed a marked reduction in adaptive thermogenesis (and insulin resistance) and increased thermogenesis in inguinal adipose, respectively (29,36). However, we did not observe changes in Ehmt1 and Tle3 mRNA expression in inguinal fat tissue from chow-fed sg/sg mice (Fig.…”
Section: E163mentioning
confidence: 40%
“…Interestingly, we examined the expression of the two very recently described genes Ehmt1 and Tle3 {transducin-like enhancer of split 3 [E(sp1) homolog, Drosophila]}, which stabilize and counter Prdm16 activity, respectively. Rodents lacking Ehmt1 and Tle3 displayed a marked reduction in adaptive thermogenesis (and insulin resistance) and increased thermogenesis in inguinal adipose, respectively (29,36). However, we did not observe changes in Ehmt1 and Tle3 mRNA expression in inguinal fat tissue from chow-fed sg/sg mice (Fig.…”
Section: E163mentioning
confidence: 40%
“…Groucho/TLE family proteins play critical roles in a wide array of developmental and cellular pathways [54]. TLE3 is expressed by placenta [55], brown and white adipose tissue [56,57], and bone marrow [25]. In addition, expression of TLE3 is known to increase with adipocyte differentiation [56].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, many of the well-characterized determinants of thermogenic function in adipocytes, including Prdm16 , Ppargc-1 , Tle3 , and Ebf2 , are differentially expressed between white and brown adipocytes. Tle3, a recently described antagonist of thermogenic gene expression, is more abundant in white adipocytes than in brown adipocytes ( 12 ). Prdm16, Pgc-1, and Ebf2, all activators of brown adipocyte development and/or thermogenic gene expression, are relatively enriched in brown adipocytes ( 9,(13)(14)(15)(16).…”
Section: Expression In White and Brown Adipose Tissue Depotsmentioning
confidence: 99%
“…Thus, the most effi cient and adipocyte-specifi c Cre line to date is the publically available Adpn -Cre BAC mouse line developed by Eguchi et al ( 23 ). This line, currently distributed through the Jackson Laboratory, has been used in a number of studies and has been demonstrated to be specifi c to adipocytes within WAT and BAT ( 12,31,112,113 ).…”
Section: Regulation Of Adipogenesismentioning
confidence: 99%